Arthroscopic Acromioclavicular Joint Fixation in Acute High-Grade Injuries Using a Single Button Over the Clavicle and a FiberTape With Modified Cinch Loop Through the Coracoid With Acromioclavicular Reduction Using a Hohmann Retractor - Ayyappan V. Nair, D.Ortho., D.N.B., M.N.A.M.S.; Bharath Bharadwaj M S, M.S. Ortho, D.N.B. Ortho; Sreejith Thampy J, M.S. Ortho; Maythilisharan Rambhojun, M.S. Ortho; Aravind Rajan, M.S. Ortho, D.N.B. Ortho; Kiran V, M.S. Ortho, M.R.C.S.; Prince Shanavas Khan, D.Ortho, M.S. Ortho (Arthroscopy Techniques)
As the existing literature attests, the treatment modalities of acute acromioclavicular (AC) joint injuries are diverse, and outcomes are often unpredictable due to a significant rate of complications. The lack of consensus even exists in the very indications for operative treatment, notably for Rockwood type 3 injuries. Historically, popular methods of fixation like hook plate and k-wires have recently given way to a suspensory type of fixation to stabilize the clavicle using the coracoid, which offers a more appealing option as they have been found to have lesser complications in comparison to the former methods. The use of hook plates mandates a second surgery for implant removal and presents risks of acromial osteolysis, rotator cuff injury, and altered scapular biomechanics, whereas k-wires are notorious for their potential to migrate in the chest wall, cause hardware irritation, and have a higher rate of loss of reduction. In this article, we describe an arthroscopic-assisted method of reducing the AC joint using a Hohman’s retractor as a lever, maintaining vertical stability by internal bracing of the coracoclavicular ligaments using a FiberTape (Arthrex) and dog button (Arthrex) and conferring horizontal stability by AC ligament reconstruction.